Regulation as modulation: autonomic flexibility as a physiological buffer in bipolar II disorder — a perspective on somatic regulation and mood stability - Purcell, Kyndra (Frontiers in Psychiatry, 2025)
Bipolar II disorder is traditionally understood as a condition of mood dysregulation, yet beneath its psychological manifestations lies a physiological rhythm often overlooked: the regulation of the autonomic nervous system. This perspective proposes that while bipolar II is not caused by a dysregulated nervous system, its course—and particularly the depth and duration of depressive episodes—is shaped by it. Drawing from psychophysiological literature and lived observation, the paper introduces the concept of regulation as modulation, suggesting that autonomic flexibility functions as a physiological buffer influencing mood stability over time. Heart-rate variability (HRV), vagal tone, and neurovisceral integration are discussed as key biomarkers linking emotional resilience and physiological coherence. When these systems are compromised, recovery from depressive episodes slows; when strengthened through conscious regulation—such as breathwork, interoception, grounding, and somatic awareness—recovery accelerates. The paper integrates evidence from existing studies on HRV and affective regulation with longitudinal self-monitoring data, noting consistent patterns between periods of autonomic dysregulation and the intensity of bipolar lows. This perspective argues that somatic regulation should be regarded as integral to treatment alongside medication and psychotherapy. Rather than framing regulation as auxiliary self-care, it should be viewed as a core therapeutic pathway that restores coherence between body and brain. For clinicians, this approach expands the framework of bipolar care; for researchers, it opens new avenues for investigating physiological mechanisms underlying mood stability. Ultimately, nervous-system regulation is not merely about achieving calm—it is about restoring rhythm, remembering safety, and redefining recovery for those living with bipolar II disorder.